PENGARUH PERSEPSI WAJIB PAJAK ATAS PEMAHAMAN PERATURAN PERPAJAKAN, AKUNTABILTAS PEMERINTAH, KESADARAN WAJIB PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Anton Robiansyah; Pratana Puspa Midiastuty; Eddy Suranta; Suparsiyem Suparsiyem (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2020)
Abstract This study aims to provide empirical evidence that understanding tax regulations, government accountability, awareness of taxpayers and tax penalties have a positive effect on taxpayer compliance. the data used in this study is primary data. Primary data was obtained from questionnaires distributed to MSMEs' Individual Taxpayers in Bengkulu City. The number of questionnaires distributed was 130 questionnaires, but only 102 questionnaires were processed. Data were analyzed using multiple linear regression analysis using the SPSS program. The results of testing hypotheses show understanding of taxation regulations and government accountability does not affect taxpayer compliance, while taxpayer awareness and tax sanctions have a positive effect on taxpayer compliance. The results of the study show that the lower the taxpayer's understanding of taxation regulations, and the lower the accountability of the government will make taxpayers increasingly disobedient in carrying out their tax obligations. Whereas, the higher the awareness of taxpayers and the more assertive the sanctions applied by the Director - General of taxation, the more obedient Individual Taxpayers who have businesses in Bengkulu City will carry out their tax obligations. Keywords: Taxpayer Compliance, Understanding Tax Regulations, Government Accountability, Taxpayer Awareness, and Tax Sanctions.